STAGE MOVEMENT AND COORDINATION: ANALYSIS OF THE TRAINING OF FUTURE ACTORS - BAXIEVA , BIYBINAZ (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
This article analyzes the role of coordination exercises in the professional training of future actors from a scientific and theoretical point of view.